The Effect of Online Learning Quality (Case Study at The Faculty of Economics and Business, Bandar Lampung University) - Aditya, Julian (International Journal Software Engineering and Computer Science (IJSECS), 2023)
During the unprecedented challenges posed by the Covid-19 pandemic, Universitas Bandar Lampung (UBL) swiftly transitioned to an online learning paradigm, notably within its Faculty of Economics and Business (FEB). This transition involved the utilization of various software tools, with WhatsApp serving as the primary communication platform and zoom as the virtual classroom medium. However, the initial adoption of Zoom-based online learning witnessed only a partial attendance of students, ranging from half to three-quarters of the anticipated enrollment, thereby influencing the overall educational experience. This research endeavors to systematically assess the impact of online education on the educational quality provided by the Faculty of Economics and Business at Universitas Bandar Lampung. Employing a quantitative methodology, the study conducted surveys on the 2020 FEB UBL student body, utilizing meticulously designed questionnaires and employing Simple Linear Regression for evaluation. The findings illuminate a noteworthy observation: (1) online learning demonstrates a discernibly positive influence on the quality of education, with an effect magnitude of 30.1%. This study contributes valuable insights into the dynamics of online education and its implications for the educational caliber within the context of Universitas Bandar Lampung's Faculty of Economics and Business